Piloting of the Concerns-based Adoption Model: Farmer Concerns About the Participatory Guarantee System in Cambodia - Meghan Mize; Cary J. Trexler; Amanda Crump; Glenn M. Young; Borarin Buntong; Karen LeGrand (Journal of International Agricultural and Extension Education, 2020)
While there is a large body of adoption and agricultural extension literature on the process of introducing a new technology, agricultural development projects are often expected to produce immediate results that do not always allow for the integration of these theories into practice. The Concerns-based Adoption Model (CBAM) is a framework that places participants at the center of the change process to identify their concerns and challenges, providing a roadmap for projects to guide individuals with the correct support for their particular stage of adoption. CBAM has typically been used for the introduction of new curriculum in formal education. But this study assessed the potential for CBAM to be applied to agriculture innovations. In this study, we adapted and piloted the CBAM “Stages of Concern” model to assess adoption of an agriculture innovation. The innovation is the Participatory Guarantee System (PGS) for Cambodian vegetable farmers. We assessed the potential for CBAM as a tool for agricultural development project management. We found that the adapted survey consistently placed farmers in the anticipated Stage of Concern. Identifying users’ Stages of Concern can inform program designers and practitioners, assisting in tailoring support across the adoption process. CBAM has the potential to inform participatory project design and give project administrators an evidence-based, systematic protocol for assessing the adoption process, adding another tool to the development practitioners’ toolbox.
Keywords: Diffusion of Innovations; adoption; project design